Penggunaan Kecerdasan Buatan (Artificial Intelligence) sebagai Bahan Pertimbangan Putusan Hakim dalam Sistem Peradilan Pidana di Indonesia - Syamsul Fatoni; Erma Rusdiana (Jurnal Penelitian Hukum De Jure, 2024)
This study evaluates the integration of artificial intelligence in the judicial processes, focusing on how technology can promote fairness in the Indonesian Criminal Justice system, where there are no specific guidelines for using AI in legal proceedings. The research follows a normative legal approach, analyzing laws and court cases and comparative methods using various legal sources and qualitative analysis methods. The findings reveal that incorporating AI in the judge's decision-making process aids in assessing information and data, facilitating optimal, effective, and efficient decision-making.  On the other hand, incorporating AI into the decision-making process of judges within the Criminal Justice System implies that judges act as a smaller version of the system itself, considering various factors such as examination records, charges, and real-life circumstances impacted by social, cultural, and economic elements. Ultimately, integrating AI into the evidential process for judicial decision-making aims to align the criminal justice system with factual situations and the goals of punishment. It is recommended that the use of AI in legal proceedings should not only focus on algorithm-based legal aspects but also take into account non-legal aspects such as humanitarian, social, and economic conditions that contribute to criminal activities. This holistic approach is crucial for ensuring alignment in the Criminal Justice System to uphold legal, moral, and societal justice.  The role of the Supreme Court is no exception in providing guidance and supervision of Judges regarding the use of technology, including legal legalization, while still paying attention to law, ethics, social values , and just legal principles.